Az erdélyi világi katolikusok helyzetértékelése az impériumváltás után (1921) - Sarnyai, Csaba Máté (Közép-Európai Közlemények, 2009)
As a response to the Rumanian concordat proposal, the Transylvanian Catholics turned to the Holy See with a memorandum in 1921. They disagreed with the concordat in many respects, therefore, they turned to the Pope. In their memorandum they revealed the state of the Transylvanian Catholic Church and community. We wish to present and analyse this document, and thus give you an insight into the impacts of the conditions which were slowly becoming stable after the change of empire on the life and religious and church days of the Transylvanian Hungarian Catholics. Finally, in our study we briefly sum up what has been realized in practice and what has been left unaccomplished from the efforts and demands expressed in the memorandum.